2015
DOI: 10.1364/oe.23.012562
|View full text |Cite
|
Sign up to set email alerts
|

Tailored optical vector fields for ultrashort-pulse laser induced complex surface plasmon structuring

Abstract: Precise tailoring of optical vector beams is demonstrated, shaping their focal electric fields and used to create complex laser micro-patterning on a metal surface. A Spatial Light Modulator (SLM) and a micro-structured S-waveplate were integrated with a picosecond laser system and employed to structure the vector fields into radial and azimuthal polarizations with and without a vortex phase wavefront as well as superposition states. Imprinting Laser Induced Periodic Surface Structures (LIPSS) elucidates the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…This, in turn, suggests a deterministic relationship between orientation and characteristic size of the surface structure and local polarization and fluence of the OV beam. It is worth noting that earlier studies mainly focused on subwavelength ripples [1,2,8,9,[14][15][16]21], while more detailed analyses of microwrinkles produced by fs Gaussian beams started only very recently [24,25]. Our findings indicate that the two structures are ubiquitous to fs laser ablation of silicon.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…This, in turn, suggests a deterministic relationship between orientation and characteristic size of the surface structure and local polarization and fluence of the OV beam. It is worth noting that earlier studies mainly focused on subwavelength ripples [1,2,8,9,[14][15][16]21], while more detailed analyses of microwrinkles produced by fs Gaussian beams started only very recently [24,25]. Our findings indicate that the two structures are ubiquitous to fs laser ablation of silicon.…”
mentioning
confidence: 59%
“…Laser-induced structures and crater profiles have been used as a direct way to diagnose intense, cylindrical vector beams in the focal plane [13][14][15][19][20][21]. Actually, there is no research addressing the optimal conditions for the formation of the diverse surface structures produced during laser irradiation of a solid target with a fs OV beam.…”
mentioning
confidence: 99%
“…However, to date, laser fabrication of biomimetic structures has been demonstrated using laser beams with a Gaussian intensity spatial profile and spatially homogeneous linear polarization18. In this context and based on the sensitivity of laser induced structures on laser polarization, it is possible to further advance the complexity of the fabricated structures via utilizing laser beams with a spatially inhomogeneous state of polarization19202122. CV beams, exhibiting tangential polarization states, are prominent examples23242526272829.…”
mentioning
confidence: 99%
“…Some authors reported about direct fs-laser LIPSS-based surface structuring by using tailored optical vortex beams with different spatial distributions of the polarization state which are generated by means of q-plates [101], SLM [102] and SLM in combination with s-waveplates [103], respectively. It was shown, that the vortex beams facilitate to extend the fabrication of even more complex and unconventional surface structures.…”
Section: Reflectivitymentioning
confidence: 99%